Enhanced Hydrogen Storage Capacity Over Electro-synthesized HKUST-1 - Witri Wahyu Lestari; Marisa Adreane; Hadi Suwarno (Institute for Research and Community Services (LPPM) ITB, 2017)
HKUST-1 [Cu3(1,3,5-BTC)2] (BTC = 1,3,5-benzene-tri-carboxylate) was synthesized using an electrochemical method and tested for hydrogen storage. The obtained material showed a remarkably higher hydrogen uptake over reported HKUST-1 and reached until 4.75 wt% at room temperature and low pressure up to 1.2 bar. This yield was compared to HKUST-1 obtained from the solvothermal method, which showed a hydrogen uptake of only 1.19 wt%. Enhancement of hydrogen sorption of the electro-synthesized product was due to the more appropriate surface area and pore size, effected by the preferable physical interaction between the hydrogen gasses and the copper ions as unsaturated metal centers in the frameworks of HKUST-1.